Ekonomi-Tanda: Analisis Awal tentang Subyektivisme dalam Teori Harga - Tarli Nugroho (Universitas Proklamasi 45 Yogyakarta, 2012)
The purpose of this article is to reveal that the price theory, as will be described later, no longer are objective, or rely on objective factors as commonly claimed by economics, but has been completely rely on subjectivity. What is the mean of subjectivity? This article attempts to outline complexity those theoretical issues.